(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study researched on the effect of collaborative learning strategy (CLS) on senior secondary school students’ anxiety and achievement in geometrical construction (GC) in Abuja. Three research question and three corresponding hypotheses were answered and tested respectively. It was a Quasi-experimental design of the pre-test, post-test, non-randomized and non-equivalent control group type involving one experimental and one control group. A total of 157 (71 males and 86 females) SS1 students were involved in the study, 74 (33 males and 41 females) students for the experimental group and 83 (38 males and 45 females) students for the control group. 4-stage sampling technique involving stratified, simple random sampling and intact class techniques were used to arrive at the samples. Two research instruments, Mathematics Achievement Test (MAT) and Mathematics Anxiety Questionnaire (MAQ) were employed for data collection. Descriptive statistics and percentages were used to answer the research questions while the hypotheses were tested using Analysis of Covariance (ANCOVA) at the level of 0.05 level of significance. The findings of the study were that i. students taught GC using CLS had lower Anxiety Mean Score than those taught without the method, ii. students taught GC using CLS had higher Achievement Mean Score than those taught without the method iii. male students scored higher in the achievement test than their female counterparts when taught GC using CLS iv. there was significant difference between the Anxiety Mean Score of students taught GC using CLS and those taught without the method v. there was significant difference between the Achievement Mean Score of students taught GC using CLS and those taught without the method, and vi. there was significant difference between male and female students’ Achievement Mean Scores when taught GC using CLS. The study recommended that all education stakeholders should endeavor to provide all necessary support to allow mathematics teachers make use of CLS in mathematics classrooms.